A comparison of lansoprazole and omeprazole based triple combinations for the treatment of Helicobacter pylori associated gastritis and peptic ulcer - Yeşim ERALP; Ahmet DOBRUCALI; Nevin BAGATUR; Aykut ÇELİK; Can DAVUTOĞLU; Murat TUNCER; Kadir BAL; Süha GÖKSEL; Hülya UZUNİSMAİL; İbrahim YURDAKUL; Ergun OKTAY (Turkish Journal of Gastroenterology, 2019)
-